A gold mine for drug discovery: Strategies to develop cyclic peptides into therapies. Issue 2 (9th October 2019) - Jing, Xiaoshu; Jin, Kang
Abstract: As a versatile therapeutic modality, peptides attract much attention because of their great binding affinity, low toxicity, and the capability of targeting traditionally "undruggable" protein surfaces. However, the deficiency of cell permeability and metabolic stability always limits the success of in vitro bioactive peptides as drug candidates. Peptide macrocyclization is one of the most established strategies to overcome these limitations. Over the past decades, more than 40 cyclic peptide drugs have been clinically approved, the vast majority of which are derived from natural products. The de novo discovered cyclic peptides on the basis of rational design and in vitro evolution, have also enabled the binding with targets for which nature provides no solutions. The current review summarizes different classes of cyclic peptides with diverse biological activities, and presents an overview of various approaches to develop cyclic peptide‐based drug candidates, drawing upon series of examples to illustrate each strategy.